KRITIK SOSIAL DALAM SURAT KOPI KARYA JOKO PINURBO SURAT KOPI BY JOKO PINURBO: A SOCIAL CRITICISM - Kun Andyan Anindita; Soediro Satoto; Sumarlam Sumarlam (LIPI Press, 2019)
Social criticism has a very big role in creating balanced, safe and peaceful civil society harmonious life. This study described social criticism in poem anthology by Joko Pinurbo, Surat Kopi, using a qualitative descriptive research method with hermeneutics and stylistics method. The research instruments were the researchers assisted by informants. To examine the poems, the researcher interpreted the poems that contained social criticism then they were described. The results showed that social criticism in the ten poems with the theme of the letter was very effective and elegant, with four types of diction used: denotation, connotation, concrete, and abstract diction. Joko Pinurbo's poems were able to reflect the social conditions of the community while capturing various problems around them. Denotation and concrete dictions were widely used in the ten poems. This avoided confusion to the reader because they utilized minimum figurative language. The message of poems could be captured clearly and explicitly; there were not many interpretations arose but still promised a depth of meaning.